Οἶκος, terre et ¥€$ : le site architectural comme ressource - Augustin Berque (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Here we show that resources exist in both a logical and ontological ternary relationship, S-I-P; in which the Earth is in the subject-substance position, S, humans in the interpreter position, I, and interpretation in the accident-predicate position, P. The result of this is reality S/P (S as P for I). Architecture is an expression of this process, in which it is established in an ecumenical and terrestrial dimension, where it must be reground, while capitalism tends to make it an abstraction.